Study on strawberry robotic harvesting system - Feng Qingchun; Zheng Wengang; Qiu Quan; Jiang Kai; Guo Rui (2012 IEEE International Conference on Computer Science and Automation Engineering, 2012)
In order to improve robotic harvesting for strawberry and reduce production cost, the harvesting robot system was designed for table-top culture, which was able to harvest fruits on both sides of itself, and it was supposed to served for sightseeing agriculture and technological show through integrating wireless operation and voice promotion. Based on machine vision and sonar technology, the independent navigation system for harvesting robot was built. The fruits were distinguished according to H(Hue) and S(Saturation) color histogram and the picking-point was located by binocular-vision system. The nondestructive operations for fruit include sucking fruit, holding and electrically cutting fruit-stem, in order to prevent damage on pericarp and disease infection. And the end-effector was positioned by a joint-type industrial manipulator. Finally, as the experimental results showed, the successful harvesting rate was 86%, and every successful harvesting operation on average cost 31.3 seconds, and the average error for fruit location was less than 4.6mm.